2020
DOI: 10.1002/elps.202000139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bile acids in human biological samples by microcolumn separation techniques: A review

Abstract: Bile acids are a group of compounds essential for lipid digestion and absorption with a steroid skeleton and a carboxylate side chain usually conjugated to glycine or taurine. Bile acids are regulatory molecules for a number of metabolic processes and can be used as biomarkers of various disorders. Since the middle of the twentieth century, the detection of bile acids has evolved from simple qualitative analysis to accurate quantification in complicated mixtures. Advanced methods are required to characterize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 165 publications
0
27
1
Order By: Relevance
“…Serum can be an argumentative decision since recoveries were found to be higher here than from plasma samples. On the other hand, the characteristics of plasma are more similar to those of whole blood due to the quenched coagulation [87]. This uncertainty could be tracked also in our study: 39.9% and 22.8% of the papers processed referred to serum and plasma, respectively, as the matrix studied; however, several times (9.6% of papers), serum and plasma were analyzed together.…”
Section: Matrices To Be Analyzed For Bile Acid Compositionmentioning
confidence: 53%
See 1 more Smart Citation
“…Serum can be an argumentative decision since recoveries were found to be higher here than from plasma samples. On the other hand, the characteristics of plasma are more similar to those of whole blood due to the quenched coagulation [87]. This uncertainty could be tracked also in our study: 39.9% and 22.8% of the papers processed referred to serum and plasma, respectively, as the matrix studied; however, several times (9.6% of papers), serum and plasma were analyzed together.…”
Section: Matrices To Be Analyzed For Bile Acid Compositionmentioning
confidence: 53%
“…In the bibliographi sources studied, no significant difference could be found between bile acid concentration in plasma and serum, with only a few exceptions; for example, Sarafian et al reported lower bile acid concentrations in plasma [86]. According to the previous reviews in thi field [87,88], there is a disagreement among authors concerning the suitability of blood serum or plasma as a matrix for bile acid analysis. Serum can be an argumentative deci sion since recoveries were found to be higher here than from plasma samples.…”
Section: Matrices To Be Analyzed For Bile Acid Compositionmentioning
confidence: 96%
“…Owing to high selectivity and potential tolerance to matrix components, CE can be used to diagnose diseases by analyzing small ions [55], organic acid-base compounds [56], amino acids [57,58], peptides [59], proteins [60][61][62] and nucleic acids [63][64][65] in biological body fluids. As a result, CE has obtained a significant position in the field of clinical medical diagnosis [66,67].…”
Section: Clinical Analysismentioning
confidence: 99%
“…Methods and technologies for the determination of endogenous and exogenous compounds in biological matrices such as plasma, urine, saliva, sweat, infected tissues, infected exudates, feces, breath, and breast milk [1][2][3][4][5][6][7][8][9][10][11][12] are under continuous development as a consequence of society's growing interest in improving the knowledge of individuals' health conditions. In this regard, the research on proper biomarkers or biological indicators of a medical state observed from outside the patient, which can be accurately and reproducibly measured, has gained special interest in the pharmaceutical and biomedical fields [13].…”
Section: Introductionmentioning
confidence: 99%